EXPLORING THE INTERSECTION OF INTELLECTUAL DISABILITIES AND MENTAL HEALTH: IMPLICATIONS FOR DIAGNOSIS AND TREATMENT: - Manish Kumar Meena (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The intersection of intellectual disabilities (ID) and mental health issues presents unique challenges and opportunities for healthcare professionals. This paper explores the prevalence, diagnosis, and treatment implications of co-occurring intellectual disabilities and mental health disorders. Through a comprehensive review of current literature and case studies, we examine how these conditions interact, the barriers to accurate diagnosis, and the best practices for treatment. Our findings suggest that integrated, multidisciplinary approaches are essential for effective management, emphasizing the need for tailored interventions and increased awareness among healthcare providers.